RENAL TUMOURS OF NON-CLEAR CELL HISTOLOGY, 10 YEARS' EXPERIENCE IN A SPECIALIZED CENTRE - Masood, Yasir; Adnan, Siddique; Fiaz, Shaukat; Sheheryar Hanif,; Cheema, Zubair Ahmad; `Mir, Khurram (Journal of Ayub Medical College Abbottabad, 2023)
Background: Non-clear cell renal cell carcinomas are uncommon renal tumours with diverse histologically and genetically defined entities. Due to limited clinical outcomes data, no standardized management approach can be offered to these patients. This study aimed to analyse outcomes of non-clear cell renal cell carcinoma after surgical resection of localized renal tumours in our population. Methods: Patients with renal tumours who underwent partial or radical nephrectomy at the department of urology, from January 2010 to December 2019 were identified and evaluated, in terms of prevalence, presentation, recurrence, and survival outcome. Results: Non-clear cell tumours were found in one-fourth of the total number of nephrectomies performed during this period for renal cell carcinoma (RCC). The mean age was 50.48±14.76 years (range 18-89 years) with 57% being of the male gender. The predominant types were chromophobe RCC, papillary RCC, and sarcomatoid RCC, in all non-clear cell renal tumours. Mean Recurrence Free Survival (RFS) for all tumours was 75.26±2.7 months. The projected 5 years RFS of papillary RCC, chromophobe RCC and sarcomatoid RCC were 94.2%, 84.3% and 62.5% respectively. Conclusion: RCC of non-clear-cell histology depicts excellent survival in patients with localized renal tumours. Furthermore, sarcomatoid RCC has worse recurrence free survival followed by chromophobe RCC and papillary RCC, in our population subset.